Unexpected Outcomes: Propagating Light Rays in the Atmosphere, a New Technique for Solving Partial Differential Equations - Neville Fowkes (Journal of Mathematical and Fundamental Sciences, 2014)
Problems that arise out of an industrial context normally have clear cut objectives, and the results are usually important in context but of limited general interest. Sometimes, however, the investigations lead to results that are both unexpected and of much broader interest. Two such investigations are described here. In the first problem an investigation of the propagation of light rays across the ocean leads to new results concerning optical distortion. In the second problem a surface tension investigation leads to an entirely new technique for solving partial differential equations.